Antibiotic-polycationic peptide conjugation as an eﬀective strategy to overcome daptomycin resistance - Rasheed, Sari; Umstätter, Florian; Mühlberg, Eric; Beijer, Barbro; Hertlein, Tobias; Klika, Karel D.; Kleist, Christian; Werner, Julia; Domhan, Cornelius; Bingel, Mara; Müller, Anna; Rausch, Marvin; et al. (Advanced therapeutics, 2025)
The benefit that antibiotics confer to the welfare of mankind is threatened by bacterial resistance. Resistance to daptomycin, a cyclic lipopeptide frequently used for the treatment of complicated bacteremia, is a prime example of this alarming situation. As the restricted number of antibacterial drug targets limits de novo development, chemical modification of existing compounds represents an alternative development option for future antimicrobials. This approach involves altering compounds to target bacteria through multiple mechanisms and/or to reinforce them against resistant strains. Herein, the conjugation of polycationic peptides to daptomycin enhances its effectiveness against a highly daptomycin-resistant laboratory strain of Staphylococcus aureus and clinical isolates of Enterococcus faecium with reduced daptomycin sensitivity. Notably, unlike daptomycin, the activity of these conjugates does not necessarily depend on the calcium concentration. In addition to regaining bacteriolytic activity, the findings indicate the acquisition of an additional or amended mode of action as evidenced by pore formation and the disruption of membrane potential. The combination of enhanced in vitro potency, in vivo activity, and tolerability highlights the potential of this drug modification strategy in combating multidrug-resistant bacteria.